Значение дефицита магния в формировании вегетативной дезадаптации у детей и подростков с патологией желудочно-кишечного тракта - Боярская, Л. Н.; Горбачева, С. В.; Потапенко, С. В.; Боярська, Людмила Миколаївна; Горбачова, Світлана Василівна; Потапенко, Сергій Валерійович; Boiarska, L. M.; Gorbachova, S. V.; Potapenko, S. V. (Запорізький державний медичний університет, 2015)
С целью выявления частоты встречаемости дефицита магния и его влияния на развитие вегетативной дезадаптации у 48 пациентов в возрасте 7–17 лет были проведены сбор анамнеза, объективное исследование, ФЭГДС, определение сывороточной и внутриклеточной концентрации Mg, холтеровское мониторирование ЭКГ. Установлено, что у 4,2% пациентов показатели и сывороточного, и эритроцитарного магния были снижены, у 19% имеет место гипоэлементоз с субоптимальным уровнем элемента в организме. У 25% детей с органическими нарушениями ЖКТ выявлены признаки магниевого гипоэлементоза, что превышает показатели детей с функциональными нарушениями ЖКТ (10%). Между показателями эритроцитарного магния и параметрами временного анализа вариабельности сердечного ритма у детей с органической патологией ЖКТ выявлена прямая, сильная корреляционная связь, в отличие от детей с функциональными нарушениями ЖКТ, не имевших магниевого дефицита. Это свидетельствует о широкой распространённости латентного дефицита магния у пациентов с органической патологией ЖКТ и усилении вегетативной дезадаптации на фоне гипоэлементоза магния. З метою виявлення частоти зустрічальності дефіциту магнію та його впливу на розвиток вегетативної дезадаптації у 48 пацієнтів віком 7–17 років здійснили збір анамнезу, об’єктивне обстеження, ФЕГДС, визначення сироваткової та внутрішньоклітинної концентрації Mg, холтерівське моніторування ЕКГ. Встановили, що у 4,2% пацієнтів показники як сироваткового, так і еритроцитарного магнію були знижені, у 19% наявний гіпоелементоз із субоптимальним рівнем елемента в організмі. У 25% дітей з органічними порушеннями ШКТ виявлені ознаки магнієвого гіпоелементозу, що перевищує показники у дітей із функціональними порушеннями ШКТ (10%). Між показниками еритроцитарного магнію та параметрами часового аналізу варіабельності серцевого ритму в дітей з органічною патологією ШКТ виявлений прямий, сильний кореляційний зв’язок на відміну від дітей із функціональними порушеннями ШКТ, які не мали магнієвого дефіциту. Це свідчить про широку поширеність латентного дефіциту магнію в пацієнтів з органічною патологією ШКТ і посилення вегетативної дезадаптації на тлі гіпоелементозу магнію. Aim. In the study of magnesium deficiency, a distinction is made between magnesium hypoelementosis and magnesium deficit. As a result, detection of the magnesium deficiency and its influence on vegetative disadaptation progression can help to correct damages in early stages and to decrease frequency of chronization of digestive tract disorders in children.Methods and results. 48 children at the ages from 7 to 17 years with complaints on sickliness, stomachache, dyspeptic symptoms were under the care. The first group contained of 28 children with organic digestive system disorders, the second – 20 children with functional digestive system disorders. In both groups serum and intracellular concentration of Mg, Holter monitoring of ECG were carried out.Conclusion. Among children and adolescents with digestive tract pathology, 4,3% of patients had magnesium deficit. Hypoelementosis was detected in 18,7% of cases, that demonstrates great prevalence of latent magnesium deficiency and the necessity of the intracellular content study. Indices of both intracellular (p≤0,05) and extracellular (p ≤0,001) magnesium in children from the 1st group were much lower than in children from the 2nd group. This demonstrates mutual influence of organic digestive tract pathology and magnesium deficit on the development and severity of pathologies. Direct and strong correlation line between intracellular magnesium level lowering and lowered indices of HRV time-line analysis was detected in the 1st group. Correlation absence in the 2nd group demonstrates the influence of magnesium deficiency on vegetative disadaptation development and provides change of digestive tract functional disorders to organic.
Значення дефіциту магнію у формуванні вегетативної дезедаптації в дітей і підлітків із патологією шлунковокишкового тракту
An importance of magnesium deficiency in the formation of vegetative disadaptation in children and adolescents with digestive tract pathology
Keywords: дефицит магния; болезни ЖКТ; подростки; дети; дефіцит магнію; хвороби ШКТ; підлітки; діти; Digestive Tract Pathology; Magnesium Deficiency; Children; Adolescents